Designing Pan-America : U.S. Architectural Visions for the Western Hemisphere - Gonzalez, Robert Alexander, 1965- (Book collections on Project MUSE., 2011)
"With this engrossing story about how architects and planners sought to express an ideal of hemispheric unity in the built environment, Gonzalez brings a fresh approach to an old question: Do the Americas have a common history? Deeply researched, cohesive, and fabulously illustrated with images of architectural projects both completed and never realized, Designing Pan-America is required reading for the new, comparative American studies." KIRSTEN SILVA GRUESZ, Professor of Literature and Director, Latino Literary Cultures Project/Proyecto culturas literarias latinas, University of California, Santa Cruz --Book Jacket